Compatibilità della finanza islamica alla normativa italiana (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Sharia compliant - 3. Murabah - 4. Ijaraha - 5. Istisna’a - 6. Sukuk - 7. Conclusioni.Islamic finance compatibility with the Italian legislationABSTRACT: Some verses of Allah that were revealed to the Prophet Mohammad in Quran were regarding economic issues. Further they were enriched in the legal framework of reference by other sources of Islamic law “Sharia” like; the Hadith (the sayings of the Prophet transmitted first orally and then transcribed), the Sunna (the tradition dictated by the words and actions of the prophet and the remembrance of the prophet statements by his first followers), and finally of Fiqh that is the Islamic jurisprudence dictated by the doctrinal interpretation of the various juridical schools. Islamic finance products which are derived from Sharia based on religious principles are very compatible with the system of traditional financial products, except for some ethical (excluded by the Sharia supervisory board) and fiscal (to avoid double taxation measures of some Islamic finance transactions), which could enhance the market attaractiveness prespective. The present study aims to investigate and identify the regulatory changes that can be implemented in the Italian legislations to make them compatible with the applicability of the typical Islamic financial contracts.